Protocol for the isolation of processed animal proteins from insects in feed and their identification by microscopy. (October 2018) - Veys, Pascal; Baeten, Vincent
Abstract: Insect processed animal proteins (PAPs) constitute a new alternative source of proteins in feed. In 2017, a closed list of insect species was authorized on the European market for use in aquafeed production. Authenticity and contamination controls will have to be set up by authorities and feed actors and supported by adequate detection methods, which are lacking. The present paper presents an original isolation and detection protocol for insect material. The protocol, based on sedimentation by a mixture of petroleum ether and tetrachloroethylene to concentrate insect particles, was developed and tested on a series of ten different aquafeeds fortified at 1% w/w with four different commercially available insect meals (from H. illucens, T. molitor, G. assimilis and A. diaperinus ). The results showed that this sedimentation protocol combined with light microscopic observation was adequate for insect detection and more efficient than the current official method. Morphological key features for reliable characterization of insect PAPs were also investigated. Structural details of cuticular fragments, such as sensilla and tracheolar structures, combined with patterns of muscle fibers, were found to constitute robust identification keys to establish the insect origin of particles. The prospective use of these markers for lower taxonomic ranking, at order level, was also addressed. Finally, the value of the markers proposed was discussed in terms of their ability to distinguish insect PAP from other types of invertebrate meal, such as that produced from marine arthropods, but also within the global framework of controls for the enforcement of the legal feed ban. Highlights: Isolation of insect fragments from a complex ingredient matrix by a double sedimentation. Morphological features useful for insect identification by light microscopy. Possibility of taxonomic sorting of edible insects is discussed for authenticity. Amendment of European regulation for official control and enforcement of feed ban.